SENI TARI: WUJUD EKSPRESI BUDAYA DAN KEKAYAAN WARISAN BANGSA - Mariam Susanti (STKIP Subang, 2026)
Dance is an art form that has long flourished across the various regions of the Indonesian archipelago. As a medium of expression, dance not only showcases the beauty of bodily movement but also reflects the values, norms, and worldviews of the communities that sustain it. This study aims to examine the status of dance as a form of cultural expression and a component of Indonesia's rich national heritage. It employs a library research method with a qualitative descriptive approach, involving the collection, review, and analysis of relevant literature. The findings indicate that dance serves a dual function: as a vehicle for aesthetic expression and as a medium for transmitting cultural values across generations. The diversity of regional dances in Indonesia—ranging from classical court dances and folk dances to contemporary creations—demonstrates a rich cultural identity that warrants preservation. However, the forces of globalization and modernization present distinct challenges to the continuity of traditional dance, necessitating sustainable preservation efforts that involve the government, educational institutions, and the community.